Directing actors : a practical aesthetics approach - Cohn, Lee Michael (Routledge, Taylor & Francis Group, 2021)
"Directing Actors: A Practical Aesthetics Approach is the first book to apply the Practical Aesthetics acting technique to the craft of directing. Lee Cohn lays out a step-by-step, no-nonsense methodology for the director that includes a deep dive into the mechanics of storytelling, the rehearsal process, working with writers, and the practical realities of the director's job. Featuring end-of-chapter exercises and an expanded glossary of terms, this book provides a clear and effective means of breaking down a script in order to tell a story with clarity, simplicity, and dramatic force, and gives directors a clear working vocabulary that will allow effective communication with actors. The techniques in this book are applicable to any theatrical style, and any media platform in which a director might work. Written in an accessible, conversation style, this book strips the process of directing down to its most essential components to explain how to become an "actor's director." A must-read for students in Directing courses and professional directors working with actors who prescribe to the Practical Aesthetics technique, as well as anyone interested in the process of working with actors, Directing Actors will help directors to get the very best their actors are capable of while approaching the work with a joyful, open spirit"--